Metabolomics: The frontier of systems biology - M Tomita [ editor ] (Springer, 2005)
Metabolism is the sum of the chemical reactions in cells that produce life-sustaining chemical energy and metabolites. In the post-genome era, metabolism has taken on new significance for biological scientists: metabolites are the chemical basis of phenotypes that are final expressions of genomic information. This book covers research on metabolomics, ranging from the development of specialized chemical analytical techniques to the construction of databases and methods for metabolic simulation. The authors have been directly involved in the development of all the subject areas, including capillary electrophoresis, liquid chromatography, mass spectrometry, metabolic databases, and metabolic simulation. Breakthrough achievements and the future of metabolome studies are described, making this book a valuable source for researchers in metabolomics in diverse fields, such as plant, animal, cellular, microbial, pharmaceutical, medical, and genetic sciences.